2012
DOI: 10.1590/s1413-78522012000600001
|View full text |Cite
|
Sign up to set email alerts
|

Resultado da neurotização do nervo ulnar para o músculo bíceps braquial na lesão do plexo braquial

Abstract: OBJECTIVE: To evaluate the factors influencing the results of ulnar nerve neurotization at the motor branch of the brachii biceps muscle, aiming at the restoration of elbow flexion in patients with brachial plexus injury. METHODS: 19 patients, with 18 men and 1 woman, mean age 28.7 years. Eight patients had injury to roots C5-C6 and 11, to roots C5-C6-C7. The average time interval between injury and surgery was 7.5 months. Four patients had cervical fractures associated with brachial plexus injury. The postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
2
10
0
7
Order By: Relevance
“…Indeed, the operated hand sometimes shows improved grip strength scores after the surgery. 1 , 2 , 9 , 13 , 14 , 17 In the present study, mean grip strength was 22.2 kg(2-42.7) which, although demonstrating a statistically significant loss of strength, mirrors results of previous studies. 7 , 9 Despite the loss of grip strength seen in the present study, overall hand function was unaffected.This result is corroborated by the patients' perceived functional deficit as assessed by the DASH score (37.87), which is in line with previously reported results.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Indeed, the operated hand sometimes shows improved grip strength scores after the surgery. 1 , 2 , 9 , 13 , 14 , 17 In the present study, mean grip strength was 22.2 kg(2-42.7) which, although demonstrating a statistically significant loss of strength, mirrors results of previous studies. 7 , 9 Despite the loss of grip strength seen in the present study, overall hand function was unaffected.This result is corroborated by the patients' perceived functional deficit as assessed by the DASH score (37.87), which is in line with previously reported results.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the presentstudy are similar to those reported in the literature for recovery of elbow flexion strength after the Oberlin procedure (77.7% ≥ MRC grade 3 and 50% ≥ MRC grade 4), 2 , 7 , 14 , 20 yet worse than some studies reporting 90-100% successful outcomes. 1 , 13 , 21 This disparity appears to be related to the fact that delayed surgical treatment – longer than 12 months after injury – is associated with poorer outcomes 2 , 6 , 8 , 17 , 21 where 5 patients (27.8%) in the present sample had a time elapsed between injury and surgery of over 12 months.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The Oberlin procedure gained notoriety due to excellent results in elbow flexion, tested and demonstrated by several authors. Currently, it is routinely used in high partial lesions of the brachial plexus, i.e., lesions that do not affect the roots of C8 and T1, which account for approximately 40% of the lesions 8, 9…”
Section: Introductionmentioning
confidence: 99%